The Far Ultraviolet Photochemistry of Alkyl-Substituted Cyclobutenes - Clark, Brady Kenneth (My University, 1987)
Electrocyclic reactions of ground and excited state hydrocarbons are well known. These transformations have helped to form a basis on which modern organic chemistry has been built on. For a variety of reasons, the photochemical transformations of one of the simplest systems, the cyclobutene system, are not well understood. This thesis attempts to provide the first thorough and systematic study of the excited state behaviour of cyclobutene in solution. The direct photochemistry of some simple, alkyl-substituted derivatives of cuclobutene is the main concern of the following chapters; the prime concern of the thesis is on the following chapters, the prime concern is on the stereochemistry of the photochemical electrocyclic ring opening process.
Ten cyclobutene systems were synthesized with a view to delineating the path of formal electrocyclic ring opening, formal (O26+O2S) cycloreversion, and the possible role of intermediates in the photochemistry of these systems. These studies have revealed that, in general, photochemical ring opening of cyclebutenes with monochromatic far ultraviolet (185, 193, and 214nm) light sources in solution proceeds non-stereospecifically to yield mixtures of all the corresponding diene geometric isomers, These results appear to contradict orbital symmetry selection rules.
Ultraviolet absorption spectra and the dependence of the photochemistry on excitation wavelength have been studies in hydrocarbon solution in order to investigate the possible involvement of two or more excited states in the direct photochemistry of these compounds. The direct photochemistry of these cyclobutene derivatives shows varying degrees of wavelength dependence throughout the series. In addition, far UV irradiations have been carried out in a hydrocarbon liquid at low temperatures, in order to study the dynamics of the formal electrocyclic ring opening process. These studies have shown that a slight barrier exists for the formally forbidden conrotatory process relative to the formally allowed disrotatory process.
It is not possible to correlate these results within the framwork of the most recently calculated (ab initio) state correlation diagrams for the ground and excited state interconversions of butadiene and cyclobutene. The results of this thesis contradict the most recent ab initio calculations, which predict that the process should proceed stereospecifically in a disrotatory fashion for the π,π* excited state of cyclobutene, indicating possibly that the theoretical work does not adequately describe the excited state character of cyclobutene or at least the theoretical results for cyclobutene itself cannot extrapolated to substituted systems.
Keywords: Organic Chemistry; Organic Chemistry